Analisis Kualitas Layanan Grab Protect, Harga Dan Promosi Terhadap Keputusan Pembelian Dalam Menggunakan Transportasi Online Pada Masa Pandemi Covid-19 (Studi Pada Mahasiswa FEB UNISMA Angkatan 2017 Jurusan Manajemen yang menggunakan Grab) - Lailatul Nurul Khasanah; Siti Asiyah; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This study aims to determine and analyze the effect of Grab Protect service quality, price and promotion on purchasing decisions using online transportation during the Covid-19 pandemic. This research is a type of explanatory research, with a quantitative approach. The research method used in this research is multiple linear regression analysis. The sample of this study used the Maholtra formula with purposive sampling technique, namely the technique of determining the sample based on certain considerations or criteria which aims to obtain a representative sample according to predetermined criteria and the number of samples obtained was 90 respondents.The results of this study indicate that simultaneously there is a significant influence between the quality of Grab Protect service, price and promotions have a significant effect on purchasing decisions using online transportation during the Covid-19 pandemic. Meanwhile, the partial test results show the quality of Grab Protect service, prices and promotions have a significant effect on purchasing decisions using online transportation during the Covid-19 pandemic. Keywords: Grab Protect Service Quality, Price, Promotion and Purchase Decision